2012
DOI: 10.3390/nu4060542
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Amino Acid Composition of Bogue (Boops boops) Fish during Storage at Different Temperatures by 1H-NMR Spectroscopy

Abstract: Nuclear magnetic resonance spectroscopy was employed to obtain information about the changes occurring in Bogue ( Boops boops ) fish during storage. For this purpose, 1 H-NMR spectra were recorded at 600 MHz on trichloroacetic acid extracts of fish flesh stored over a 15 days period both at 4 °C and on ice. Such spectra allowed the identification and quantification of amino acids, together with the main organic acids and alcohols. The concentration of acidic and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…The effects of storage temperature on the amino acid profile of Bogue fish was studied by Ciampa et al (2012) using NMR metabolomics on spectra acquired at 600 MHz. In this case, the novelty of the approach concerned the normalisation algorithm based on the total nucleotide amount, which constituted a pool of interconverting metabolites.…”
Section: Using Metabolomics To Identify the Geographical Origin Of Fomentioning
confidence: 99%
“…The effects of storage temperature on the amino acid profile of Bogue fish was studied by Ciampa et al (2012) using NMR metabolomics on spectra acquired at 600 MHz. In this case, the novelty of the approach concerned the normalisation algorithm based on the total nucleotide amount, which constituted a pool of interconverting metabolites.…”
Section: Using Metabolomics To Identify the Geographical Origin Of Fomentioning
confidence: 99%
“…This change in the limiting aminoacid could be a consequence of enzymatic reactions and/or bacterial growth during storage [46]. On the other hand, the frozen carp with EC continued to present a higher concentration in the aforementioned aminoacids (Iso, Met + Cys, and Val), thereby presenting a protective effect in Lys, which results in great benefit since fish could be maintained as an important source of this aminoacid after 5 months of storage in the freezer [42, 47].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, product quality analysis, for example, in response to different storage conditions, can benefit from such an approach. This was exemplified by Ciampa et al (2012), who observed that proteolysis in the flesh of refrigerated bogue (Boops boops) proceeded slowly during the first few days, but then accelerated due to microbial action. Another angle that highlights the potential use of metabolomic analyses relates to identification of altered metabolite fingerprints; for instance, in response to super-intensive farming, as was demonstrated in the shrimp Litopenaeus vannamei (Schock et al 2013)-it is conceivable that particular metabolites can become valuable for diagnostic purposes, for example in the context of health monitoring.…”
Section: Metabolomicsmentioning
confidence: 93%